Phase Behavior and Heat Capacity of {DPnP + Water} Mixtures at the Temperature Range of 273.15–338.15 K - Mariola Tkaczyk; Henryk Piekarski; Paweł Góralski (Journal of Chemistry)
The differential scanning calorimetry method (DSC) was used to examine the miscibility in the {dipropylene glycol propyl ether (DPnP) + water} system. Based on recorded curves of differential heat flow on temperature, HF =f(T), the range (composition, temperature) of the occurrence of miscibility gap, the values of lower critical solution temperature (LCST), and critical concentration were determined. On the basis of the experimentally determined specific heat capacity data the partial molar heat capacities (Cp,2) of DPnP in the mixtures with water were calculated. Analyzing changes in the course of Cp,2=f(x2) function, the boundary of transition from a homogeneous solution was determined, in which the monomers of amphiphile dominate, to the region, in which aggregates of the cluster type appear.